VD_FINDINFO Arrêt / 2016 / 534 vom 13. Juni 2016 - VD Tribunal cantonal (2016)
RÉVISIONDÉCISION, RECONSIDÉRATION, ACTIVITÉ LUCRATIVE INDÉPENDANTE, STATUT DE L'ASSURÉASSURANCE SOCIALE | 9 Cst., 5 LAVS, 10 LPGA, 12 LPGA, 49 LPGA, 51 LPGA, 53 LPGA